Explaining the commitment of family planning fieldworkers in Bangladesh - Andaleeb, Syed Saad (© 1996 Guttmacher Institute, 2016)
This article was published in the International Family Planning Perspectives [© 1996 Guttmacher Institute] and the definite version is available at : http://doi.org/10.2307/2950796 The Journal's website is at: http://www.jstor.org/stable/2950796